Pseudopheochromocytoma Associated with Domestic Assault - H. M. Le; G. Carbutti; D. Ilisei; E. Bouccin; X. Vandemergel (Case Reports in Cardiology)
Pseudopheochromocytoma has a clinical presentation that is similar to pheochromocytoma. It manifests itself with paroxysmal hypertension crises, associated with various symptoms such as headaches, chest pain, nausea, palpitations, and dizziness. Patients are usually asymptomatic in between the crises. Unlike pheochromocytoma, there is no catecholamines overproduction in this pathology: hypertensive peaks are caused by a hyperactivation of the sympathetic nervous system, which is often triggered by a psychological trauma in the past. Treatment of pseudopheochromocytoma can be challenging due to normal blood pressure values in between the hypertensive peaks; it includes alpha- and beta-blockers for moderate crises and prevention and must be combined with psychopharmacologic agents such as anxiolytics or antidepressant drugs. Psychotherapy and dietetic treatment are also crucial in pseudopheochromocytoma management.